2010
DOI: 10.1016/j.jvs.2010.03.031
|View full text |Cite
|
Sign up to set email alerts
|

The Vascular Study Group of New England Cardiac Risk Index (VSG-CRI) predicts cardiac complications more accurately than the Revised Cardiac Risk Index in vascular surgery patients

Abstract: The RCRI substantially underestimates in-hospital cardiac events in patients undergoing elective or urgent vascular surgery, especially after LEB, EVAR, and OAAA. The VSG-CRI more accurately predicts in-hospital cardiac events after vascular surgery and represents an important tool for clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
164
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(181 citation statements)
references
References 26 publications
9
164
1
7
Order By: Relevance
“…The robust association between the PRFI in predicting mortality or respiratory failure in this study is consistent with individual variables comprising the PRFI such as older age, albumin level, renal dysfunction, and thoracic surgery diagnosis individually having demonstrated predictive value in other prospective studies [15][16][17][18]. Also consistent with this study is a recent systematic review and cohort study which demonstrated that the RCRI was poor to moderate in discriminating postoperative cardiac events in populations of vascular noncardiac and mixed noncardiac surgical patients [19,20].…”
Section: Discussionsupporting
confidence: 90%
“…The robust association between the PRFI in predicting mortality or respiratory failure in this study is consistent with individual variables comprising the PRFI such as older age, albumin level, renal dysfunction, and thoracic surgery diagnosis individually having demonstrated predictive value in other prospective studies [15][16][17][18]. Also consistent with this study is a recent systematic review and cohort study which demonstrated that the RCRI was poor to moderate in discriminating postoperative cardiac events in populations of vascular noncardiac and mixed noncardiac surgical patients [19,20].…”
Section: Discussionsupporting
confidence: 90%
“…Yine EVAR açık ameliyata oranla, kalple ilgili komplikasyonların azalması (%3,1'e karşı %21,8) ve daha düşük perioperatif mortalite oranı (%1,7'e %4,7) ile de ilişkilidir. Bu nedenlerle EVAR aort anevrizma onarımı için özellikle riskli hastalarda cazip bir tedavi stratejisidir (15)(16)(17)(18).…”
Section: Discussionunclassified
“…Из 18 больных, перенесших инфаркт миокарда, 12 (66,7%) не имели ишемических симпто-мов для его подтверждения, диагноз был установлен при оценке уровня тропонинов в плазме крови [11]. К подобному выводу пришла и группа исследовате-лей в регистре VSG-CGRI, в результате они разрабо-тали свой прогностический индекс, более точно предсказывающий развитие кардиальных осложне-ний при сосудистых операциях [12]. Более гибкий подход к определению показаний для предоперационного кардиального обследования у больных перед операциями на некоронарных арте-риальных бассейнах предложен в национальных рекомендациях ВНОК [3].…”
Section: Discussionunclassified